ANALISIS DAYA SAING DAN STRATEGI INDUSTRI MAKANAN DAN MINUMAN INDONESIA DI ERA MASYARAKAT EKONOMI ASEAN - Rosnawintang Rosnawintang; Suwandi Suwandi; Nur Azisah (Universitas Halu Oleo, 2015)
The purpose of this study to determine the competitiveness of the food and beverage industry Indonesia period 2011-2015 and its strategy in the era of the ASEAN economic community. The type of data in this research is secondary data. The analytical tool used to measure the competitiveness of Indonesian food and beverage industry is the analysis of revealed comparative advantage while to examine strategies for Indonesian food and beverage industry using SWOT analysis.The results using analysis revealed comparative advantage shows Products Indonesian food and beverage industry has a level of competitiveness which tends to fluctuate, bakery products and pastries have the highest level of competitiveness in Vietnam later confectionery products in Vietnam and coffee products in Thailand, the next product Tea in Malaysia last is the product of chocolate and chocolate preparations in Thailand.Â The strategy can be developed for the Indonesian food and beverage industry in the era of ASEAN economic society based on SWOT analysis is a strategic approach to new markets and market penetration for long. The second strategy of expanding the product promotion. The third strategy for increasing the ability of employees or workers. and the fourth customer service strategies and renewable products.